(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This research is read in two readings cash prizes for the hangings carried out by each of Yousef Yousef in his book (Research in pendants), and WaficKhansh in his book (distant horizons). This research confirms that the pendants superior text, open readings does not end, it seeks to detect psychological and intellectual backgrounds, and monetary trends adopted by Nakdan in Qratehma Alrasd components of the poetic text, Mufsrtin, Almaolten language structure in order to accommodate the text that Amadmrat. The aim of this study highlight the importance of these two readings Alnkaditin which Tnolta pendants based on the poets link to their communities at times, and at other times creative moment; in addition to finding critical links between the two readings in order to provide a comprehensive reading of the poetic text, relying on the descriptive analytical approach.